2022
DOI: 10.1080/20008198.2022.2029333
|View full text |Cite
|
Sign up to set email alerts
|

Lay causal beliefs about PTSD and cultural correlates in five countries

Abstract: Background To date, cultural clinical research has primarily focused on differences between ethnic groups when investigating causal beliefs about mental disorders. While individual as well as contextual factors are considered important for gaining a better understanding of cultural influences, research on causal beliefs about post-traumatic stress disorder (PTSD) and cultural correlates in laypersons is scarce. Objective This study aimed at gain a better understanding o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Sample characteristics for the total sample as well as by country are given in Table 1 . The sample has been described in more detail elsewhere [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample characteristics for the total sample as well as by country are given in Table 1 . The sample has been described in more detail elsewhere [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Third, the 'motivation' to engage in psychological support may be influenced by beliefs about mental health [18]. Research has demonstrated that complex cultural frameworks inform individual health beliefs and symptom expression [19,20]. Taken together, it is important to understand how patients conceptualise psychological symptoms and their beliefs about the usefulness, and availability, of psychological treatment in this context.…”
Section: Introductionmentioning
confidence: 99%